And the winner is ... 'thrown under the bus'. (World Today)
The article discusses current political scenario in Great Britain. Topics include injustice suffered by the Waspi women, with no attempt to explain that it stands for Women Against State Pension Inequality, Prime Minister's betrayal of Northern Ireland's Democratic Unionist Party, and Labour Party's allegation regarding hacking attack.